Struttura non-matrixed e teatro delle immagini: L’esplorazione del linguaggio nella performance art e nel Nuovo Teatro - Borriello, Marilena (Mimesis Journal, 2016)
The term performance generally refers to actions both in experimental art and in theatre; two different areas by tradition, but determined by certain common elements that make it difficult to link the word to the former or the latter. Although versatility and diversity are the its main aspects, the performative language has progressively imposed its own form determined by the autonomous complex relationship between word and image. Taking into account this aspect and retracing the Michael Kirby’s concepts of non-matrixed structure and the Bonnie Marranca’s notion of theatre of images, this essay aims to envisage the performance as an art form that could bring attention to the value of the experience and to re-establish a link between the aesthetics of the authoring and the aesthetics of perception.